SANITARY SURVEILLANCE AND DYPLOSTOMIDAE IN FISHES ON ORÓS DAM, CEARÁ - Silva Siqueira, Raoane; de Lima Cunha, Jane Cris; Longo Ribeiro Vilela, Vinícius (Cadernos ESP, 2023)
Report a investigation carried by the Sanitary Surveillance Department (SSD) for dyplostomidae, parasitosis in fish eyes. The descriptive, qualitative, observational study was based from complaints, thougth direct searches and situational diagnoses maked by SSD in Orós dam, Brazil. The fish received carrying the parasitosis were necropsied and samples of the organs collected for parasitological identification and histopathological analysis. Factors predisposing to the parasite’s cycle were found in the water reservoir: piscivorous birds, abundant vector molluscs, eutrophic waters from fish farming, cattle farming and domestic sewage. Laboratory analyzes identified Austrodiplostomum spp., an opportunistic trematode without impact in human health. Once the investigation was concluded, producers and traders began to eviscerate fish in appropriate place and stow the fish correctly. The diagnosis of dyplostomidae is unprecedented in this region and the swift elucidation of the case carried out by the municipal SSD contributed to restructuring the local food and economic security.